Analysis of diagnostic informative value of the Full Outline of UnResponsiveness Scale in patients with spontaneous supratentorial intracerebral hemorrhage - A. A. Kuznietsov (Zaporožskij Medicinskij Žurnal)
The main purpose of the study was to verify the diagnostic informative value of the Full Outline of UnResponsiveness Scale in patients with SSICH based on the comparison with neuroimaging criteria of midline shift severity.